Immunisation of guinea-pigs with circulating immune complexes from patients with rheumatoid arthritis. Issue 5 (October 1984) - Hack, C E; Lim, H G; Aalberse, R C
Abstract : Sixteen guinea-pigs were immunised with immune complexes isolated from serum of nine patients with rheumatoid arthritis. The resulting antisera were analysed by radioimmunoassays. All guinea-pig sera were extensively absorbed with normal human serum. After this absorption eight guinea-pig sera contained antibodies specific for immune complexes isolated from the sera of three patients. One of these antisera reacted not only with immune complexes (and serum) from the corresponding patient but also with immune complexes (and sera) from other patients with rheumatoid arthritis. The antigen(s) to which the guinea-pig antibodies were directed sedimented as IgM, and they bound to IgG Sepharose. Therefore the guinea-pig sera were absorbed with IgM-rheumatoid factors isolated from the serum of the corresponding patient. After this absorption, the guinea-pig sera had lost their reactivity with immune complexes. We conclude that these antisera did not detect an exogenous antigen in immune complexes from patients with rheumatoid arthritis. The positive reactions found were due to antibodies specific for (idiotypic?) antigenic determinants on IgM-rheumatoid factors.